2016
DOI: 10.1001/jamaophthalmol.2016.4272
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of 3 Distinct Retinal Plexuses by Projection-Resolved Optical Coherence Tomography Angiography in Diabetic Retinopathy

Abstract: IMPORTANCE Projection artifacts in optical coherence tomography angiography (OCTA) blur the retinal vascular plexuses together and limit visualization of the individual plexuses.OBJECTIVE To describe projection-resolved (PR) OCTA in eyes with diabetic retinopathy (DR) and healthy eyes. DESIGN, SETTING, AND PARTICIPANTSIn this case-control study, patients with DR and healthy controls were enrolled in this observational study from January 26, 2015, to December 4, 2015, at a tertiary academic center. Spectral-dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
154
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 173 publications
(163 citation statements)
references
References 29 publications
7
154
1
1
Order By: Relevance
“…Ugyanakkor az OCT-angiográfia nem alkalmas az erekből történő folyadékszivárgás vizualizálására, és jelenleg nem képes a perifériás retinaterületek leképezésére sem [37]. Jelen tanulmányunkban a macula területén a felszíni kapillárisér-hálózat sűrűségét elemeztük, miután a mély kapillárisér-hálózat sűrűségének vizsgálata jelenleg még nem kellően megbízható a projekciós műtermé-kek miatt [38,39].…”
Section: Következtetésunclassified
“…Ugyanakkor az OCT-angiográfia nem alkalmas az erekből történő folyadékszivárgás vizualizálására, és jelenleg nem képes a perifériás retinaterületek leképezésére sem [37]. Jelen tanulmányunkban a macula területén a felszíni kapillárisér-hálózat sűrűségét elemeztük, miután a mély kapillárisér-hálózat sűrűségének vizsgálata jelenleg még nem kellően megbízható a projekciós műtermé-kek miatt [38,39].…”
Section: Következtetésunclassified
“…An experienced masked grader qualitatively examined the en face DCP angiograms [7]. The dilated capillaries were localized using a modified Early Treatment of Diabetic Retinopathy Study (ETDRS) grid [24], dividing the 3 × 3 mm angiogram into a central 500 micron circle, and the remaining area into superior, inferior, nasal, and temporal quadrants.…”
Section: Evaluation Metricsmentioning
confidence: 99%
“…We previously showed that applying PR-OCTA to visualize the individual layers, the sensitivity of detecting DR and determining its severity with automated algorithms can be improved [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It enables a high sensitivity, high speed and non-invasive way to acquire the cross-sectional reflectivity profile of a sample [5,6]. Besides information on the layer structure, optical coherence tomography angiography (OCTA) algorithms [7,8] allow depth-resolved visualization of the retinal and choroidal blood circulation [9][10][11] and identification of abnormal vascular and blood flow changes [12] in ocular diseases such as glaucoma [13][14][15], age-related macular degeneration [16,17], and diabetic retinopathy [18,19]. Additionally, OCT has become a powerful research tool for 3D imaging of complex myocardial activities in early-stage embryonic hearts with high spatial and temporal resolution.…”
Section: Introductionmentioning
confidence: 99%